HIGH-TITANIUM FERROPICRITES. SPECIAL IGNEOUS ROCKS OF THE EARLY TO LATE PRECAMBRIAN TRANSITIONAL STAGE - Sharkov Ye.V.; Smol'kin V.F. (My University, 1989)
The boundary dated at 200 to 1800 m.y. marks an event that is of fundamental importance in the Earth's history and separates the early stages of planetary evolution from the Neogaean with its present type of geodynamics. This boundary is expressed on a global scale not only in the results of radiologic dating of rocks of the Earth's crust and upper mantle, but also in a number of important geologic events. That was the time when much of the Earth's crust became consolidated, and when continental rifting began in various places (Karelia-Kola region. Labrador trough. It was also the time when the first distinct collision structures, like the Lapland deep fault on the Baltic shield were formed, and the first reliably identified Svecofennian ophiolite complexes appeared, such as the 1.96-b.y.-old Jormua in Finland. The high-titanium ferropicrites and their intrusive analogs were formed at virtually the same time as old cratons, so the problem of their origin can be posed in the context of the Earth's evolution as a whole.
Keywords: Precambrian; Precambrian; Докембрий